The Influence of Student Management on Student Discipline - Sumaiya G.R. Dg. Mabone; Rustina Rustina; Masmur M. (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to examine the influence of student management on student discipline at SD Inpres Masigi, Parigi Moutong Regency. The research employed a quantitative approach with an ex-post facto survey design. The population consisted of 75 students from grades IV, V, and VI, and all members of the population were selected as research samples using a saturated sampling technique. Data were collected through questionnaires, observation, and documentation. The research instruments were tested for validity and reliability before being administered. Data analysis techniques included descriptive statistics, normality tests, linearity tests, simple linear regression, and coefficient of determination analysis using IBM SPSS. The findings revealed that student management was categorized as moderate, with 68% of respondents falling into the medium category, while student discipline was also in the moderate category, with 56% of respondents categorized as medium. The normality and linearity tests indicated that the data met the statistical assumptions required for regression analysis. The results of the simple linear regression test showed a significant positive effect of student management on student discipline, with the regression equation Y = 8.909 + 0.653X. Furthermore, the coefficient of determination (R²) was 0.441, indicating that student management contributed 44.1% to student discipline, while the remaining 55.9% was influenced by other factors outside the study. These findings emphasize the importance of structured and effective student management practices in fostering student discipline and creating a conducive learning environment